Analysis of Effectiveness, Efficiency, and Contribution of Regional Tax Revenue and Regional Levies to Original Regional Income (PAD) of Kerinci Regency Year 2019-2021 - Nina Noviani; Yudi; Muhammad Gowon (PT FORMOSA CENDEKIA GLOBAL, 2024)
The puproses of this research is to determine the extent of the effectiveness, efficiency and contribution of regional taxes and levies to Kerinci Regency's Original Regional Income. This research was conducted at the Regional Financial and Revenue Management Agency (BPKPD) Kerinci Regency, Jambi Province. This research uses a quantitative descriptive approach with data collection techniques, namely observation. The data used is secondary data in the form of reports on the realization of Kerinci Regency regional tax and levy revenues. The research results show that (1) The effectiveness of regional taxes and levies in Kerinci Regency is less effective (2) The efficiency of collecting regional taxes and levies is categorized as efficient (3) The contribution of regional taxes and levies is categorized as very less contributing. So it is hoped that the Regional Financial and Revenue Management Agency (BPKPD) of Kerinci Regency can optimize regional taxes and levies in Kerinci Regency